2022
DOI: 10.1097/01.asw.0000824564.25976.c8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Burden of Inpatient Wound Care in Internal Medicine Units During the First Wave of COVID-19 Outbreak

Abstract: Objective: To explore the clinical burden and epidemiologic profile of hospitalized patients with wounds during the first wave of COVID-19.Methods: A retrospective and observational study was conducted to analyze the inpatient episodes of wound care in the University Hospital of Salamanca (Spain) during the initial COVID-19 crisis from March 1, 2020, to June 1, 2020. Data were collected from nursing care reports and clinical discharge reports. Included patients were 18 years or older, had a hospital length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…In the initial COVID-19 cohorts, HAPIs increased around the globe and at our institution. Nieto-Garcia et al reported a 2 times higher risk of pressure injury for patients admitted with COVID-19 from March to June 2020 (same as our cohort 1) 18 . In our study, mechanical ventilation and proning were independent predictors of HAPIs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the initial COVID-19 cohorts, HAPIs increased around the globe and at our institution. Nieto-Garcia et al reported a 2 times higher risk of pressure injury for patients admitted with COVID-19 from March to June 2020 (same as our cohort 1) 18 . In our study, mechanical ventilation and proning were independent predictors of HAPIs.…”
Section: Discussionsupporting
confidence: 74%
“…Nieto-Garcia et al reported a 2 times higher risk of pressure injury for patients admitted with COVID-19 from March to June 2020 (same as our cohort 1). 18 In our study, mechanical ventilation and proning were independent predictors of HAPIs. Multiple other studies identified proning as a contributing factor for increased HAPIs in patients with COVID-19, leading to the development of specialty proning teams, proning procedures with positioning supports, and increased use of various products to prevent HAPIs associated with proning.…”
Section: Discussionsupporting
confidence: 50%